Transcriptome‐wide association study of breast cancer risk by estrogen‐receptor status. Issue 5 (1st March 2020) - Feng, Helian; Gusev, Alexander; Pasaniuc, Bogdan; Wu, Lang; Long, Jirong; Abu‐full, Zomoroda; Aittomäki, Kristiina; Andrulis, Irene L.; Anton‐Culver, Hoda; Antoniou, Antonis C.; Arason, Adalgeir; Arndt, Volker; et al.
Abstract: Previous transcriptome‐wide association studies (TWAS) have identified breast cancer risk genes by integrating data from expression quantitative loci and genome‐wide association studies (GWAS), but analyses of breast cancer subtype‐specific associations have been limited. In this study, we conducted a TWAS using gene expression data from GTEx and summary statistics from the hitherto largest GWAS meta‐analysis conducted for breast cancer overall, and by estrogen receptor subtypes (ER+ and ER−). We further compared associations with ER+ and ER− subtypes, using a case‐only TWAS approach. We also conducted multigene conditional analyses in regions with multiple TWAS associations. Two genes, STXBP4 and HIST2H2BA, were specifically associated with ER+ but not with ER– breast cancer. We further identified 30 TWAS‐significant genes associated with overall breast cancer risk, including four that were not identified in previous studies. Conditional analyses identified single independent breast‐cancer gene in three of six regions harboring multiple TWAS‐significant genes. Our study provides new information on breast cancer genetics and biology, particularly about genomic differences between ER+ and ER− breast cancer.